2020
DOI: 10.1002/smll.202003098
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Slantwise Aligned Dion–Jacobson Phase Perovskite Solar Cells Based on Trans‐1,4‐Cyclohexanediamine

Abstract: The efficiency of perovskite solar cells (PSCs) has been boosted from power conversion efficiency (PCE) of 3.8% [1] to 25.2% [2] in ten years, providing the further possibility for commercialization. The general chemical formula for 3D perovskite is known as ABX 3 , where A typically is methylammonium (MA +), formamidinium ions (FA 2+), B is lead or tin, and X is usually halide element (I, Cl, and Br). Conventionally, formamidinium and methylammonium ions mixed (FAMA-mixed), [3] cesium, formamidinium and methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 38 publications
(53 reference statements)
2
33
0
Order By: Relevance
“…[ 7,8 ] It is found that the ultrathin thickness and large specific area of nanosheets can bring perovskites some attractive optical, photochemical, or electric properties (e.g., high photoluminescence efficiency, large photoconductive gain, etc. ), which expands their potential for fabricating devices with various photo‐induced functionalities such as solar cells [ 9–12 ] and light‐emitting diodes, [ 13,14 ] as well as high‐performance photodetectors (PDs). [ 15,16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] It is found that the ultrathin thickness and large specific area of nanosheets can bring perovskites some attractive optical, photochemical, or electric properties (e.g., high photoluminescence efficiency, large photoconductive gain, etc. ), which expands their potential for fabricating devices with various photo‐induced functionalities such as solar cells [ 9–12 ] and light‐emitting diodes, [ 13,14 ] as well as high‐performance photodetectors (PDs). [ 15,16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, solar cells built with trans-1,4-cyclohexanediamine retained 95% PCE after >1000 h of storage in 50-60% humidity. [139] In the same study, solar cells incorporating a linear alkyl chain-1,6-diaminohexane-dropped to 41% of initial PCE in less than 200 h.…”
Section: Phase Stability Of Dion-jacobson Perovskitesmentioning
confidence: 89%
“…The higher stability of the DJ materials translates into significantly longer lifetimes reported for DJ-phase PSCs, as compared to the RP counterparts. [25,138,139] Specifically, the more rigid and robust DJ structure has been shown to provide improved stability of devices toward humidity, heat, and light. [139][140][141][142] For example, replacing the pentylammonium PA cation with 1,3-propanediammonium DJ-spacer in (PDA) (MA) 3 Pb 4 I 13 results in remarkable stability enhancement toward humidity.…”
Section: Phase Stability Of Dion-jacobson Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…[130] Other modification engineering has also been applied in DJ phase PSCs, such as molecule doping (Cl − , SCN − ), antisolvents, and hot casting processing, which broaden the horizons of 2D perovskite for achieving high photovoltaic performance of PSCs. [129][130][131][132][133][134][135][136][137][138][139][140][141][142]…”
Section: Dj Phase Pscsmentioning
confidence: 99%